Current State of Post-Disaster Reconstruction Projects: A Bibliometric Analysis - Baarimah, A.O. (Institute of Electrical and Electronics Engineers Inc., 2021)
A growing number of large-scale disasters and inefficiencies in reconstruction projects in recent years necessitated the development of guidelines for completing successful post-disaster reconstruction (PDR) projects. Reconstruction projects are still facing several challenges such as time and cost overruns and low quality due to several issues during the implementation. Various studies in construction industry have been undertaken on PDR projects. However, there has been no attempt of scientometric analysis to explore the holistic understanding of the current state of PDR research. The aim of this research is to conduct a bibliometric analysis of the available PDR literature and to provide a picture of the research status from 2010 to August 2021. There were 352 documents extracted from the database of Scopus. VOSviewer tool was used to visualize the literature contained through countries, scientific journals, and keywords. The outcomes showed that 'Reconstruction', 'Resilience', 'Build Back Better', and 'Project Management' were lately risen to prominence as mainstream topics in this field and piqued the curiosity of academics, which may represent future research possibilities as well. Moreover, based on the most keywords frequently used, three important research domains linked with post-disaster have been identified, including 'Post-Disaster Reconstruction', 'Housing', and 'Vulnerability'. Accordingly, the explanations related to research outcomes, recommendations for future studies have been provided on the projects of PDR. The result from this review will contribute to the field of PDR by assisting scholars and practitioners to explore the current state and path the way for future trends of PDR research. Â© 2021 IEEE.